Revision of Nearctic Microcercis Beschovski (Diptera: Chloropidae), with Synonymy of Incertella Sabrosky - Foster, George A. (Zootaxa, 2024)
Nearctic species of Incertella Sabrosky, 1980 are transferred to Microcercis Beschovski, 1978 due to the synonymy of the type species I. incerta (Becker, 1912) with M. albipalpis (Meigen, 1830). The ten species treated are M. albipalpis (Meigen) = M. incerta (Becker) syn. n., M. bispina (Malloch), M. dorsata (Loew), M. infesta (Becker), M. insularis (Malloch), and M. minor (Adams), [all are new combinations], and the four new species: M. laytoni sp. n., M. murphyi sp. n., M. johanni sp. n. and M. trifeminarum sp. n. A generic diagnosis is provided, as are species diagnoses and descriptions and a key to Nearctic Microcercis. Lectotypes are designated for M. infesta, and M. insularis. Incertella ovalis (Adams) is moved to Conioscinella Duda comb. n. Photographs illustrating the habitus of all species, male genitalia photos of most species, and scanning electron microscope (SEM) photos of specific features are provided. Material from Canada, the United States, and Mexico is recorded.